Digital justice and its impact on the functioning of procedural rivalry in UAE law - Allouzi, Adel Salem (Research Journal in Advanced Humanities, 2024)
This research addresses digital justice and its impact on procedural rivalry within UAE law through an applied theoretical study. It examines the legal aspects of Ministerial Decree No. 260 of 2019, which provides procedural guidelines for conducting litigation using electronic means and telecommunications in civil proceedings. The study explores both technical and legal aspects of digitization in civil litigation, including its role in initiating adversarial proceedings, judicial deliberation, sentencing, and issuing timely and provisional orders. Additionally, this research evaluates the effectiveness of the digital framework in judicial work, analyzing its impact on adversarial litigation and procedural efficiency. The study integrates empirical insights to assess how digital justice influences litigation dynamics and the overall functionality of judicial procedures.